2021
DOI: 10.3390/ani11010127
|View full text |Cite
|
Sign up to set email alerts
|

Do Domestic Pigs Acquire a Positive Perception of Humans through Observational Social Learning?

Abstract: Farm animals can perceive humans positively by observing another animal being positively handled. This study evaluated whether pigs acquire a positive perception of humans after observing either a high or low socially ranked conspecific receiving gentle handling. Seventy-five 21-week-old pigs were housed in 15 nursery pens (five pigs/pen) and randomly assigned to one of three pen treatments: Dominant Demonstrator Group (DDG), Subordinate Demonstrator Group (SDG) and Control Group (CG). Pigs from DDG and SDG ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 71 publications
0
22
2
Order By: Relevance
“…Studies on poultry have shown that visual contact with an experimenter reduces birds' fear of handling [29], and can be more effective at reducing fear of humans than gentle tactile contact [30]. Recent research has also demonstrated that pigs' fear of humans is reduced when they observe a human stroking other pigs [31]. It is therefore possible that any treatment effects on responses in the HAT were diluted as a result of control sows receiving additional visual exposure to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on poultry have shown that visual contact with an experimenter reduces birds' fear of handling [29], and can be more effective at reducing fear of humans than gentle tactile contact [30]. Recent research has also demonstrated that pigs' fear of humans is reduced when they observe a human stroking other pigs [31]. It is therefore possible that any treatment effects on responses in the HAT were diluted as a result of control sows receiving additional visual exposure to humans.…”
Section: Discussionmentioning
confidence: 99%
“…This is true for socially housed animals, but also for singly housed animals that have visual or auditory contact with other individuals. Thus, it is worth thinking in very broad terms about an animal's social world and how social cues-both from conspecifics and human care takers-can and will influence animals' decision making, behavior, and welfare [86,87]. Importantly, emotional contagion can be leveraged in beneficial ways.…”
Section: Socialization and Seeding New Cultural Traditionsmentioning
confidence: 99%
“…Moreover, informal human-animal interactions may not always confer welfare benefits [191], although playful handling of rats has been shown to reduce the rats' fear of caretakers [192]. It has been shown that the identity and experience of the person providing care can influence an animal's welfare [193][194][195] and a recent study with pigs demonstrated that animals that had seen a stockperson using gentle handling techniques on pen mates were more likely to approach and make contact with the stockperson than pigs who had not received such social information [87]. From this, the authors [87] concluded that "pigs can learn to perceive humans positively through observational social learning" (p. 127).…”
Section: Spontaneous Social Learning Of Unanticipated or Negative Behmentioning
confidence: 99%
See 1 more Smart Citation
“…C and +HC litters were allocated to opposite ends of each room in order to minimise any carry-over effects of the positive handling treatment. In particular, it was important to minimise the amount of visual exposure to humans that C litters received through the imposition of the +HC treatment, as fear of humans is reduced in pigs that observe positive handling of other pigs [32]. Thus, in the farrowing crate room where 2 parallel rows of crates were used, non-experimental litters (also from first parity sows) were allocated in between +HC and C litters (Figure 2b).…”
Section: Human Contact Treatment Allocationmentioning
confidence: 99%